2018
DOI: 10.4194/1303-2712-v18_5_01
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Concentrations of eleven trace elements (Zn, M n, Cu, Fe, Cr, Ni, Co, Hg, Pb, Cd and As) as well as the principal components of fish flesh (water%, dry matter%, fat%, protein%, ash% and Ca and M g concentration) were determined in muscles of six fish species (Scardinus knezevici, Alburnus scoranza, Cyprinus carpio, Rutilus prespensis, Anguilla anguilla and Perca fluviatilis) collected from Skadar Lake in 2016. This study, being the first of its kind in fish from M ontenegrin lakes, gave the following overall r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 14 publications
6
13
1
Order By: Relevance
“…In line with other studies (Jovičić et al 2015;Léopold et al 2015;Jia et al 2017), we found only a few significant relationships between metal concentrations and total length (a proxy for age). In line with previous literature (Rakocevic et al 2018), significant relationships were mainly found for essential elements, while no clear or not-significant relationships were found for the non-essentials. The absence of clear patterns is likely due to fish belonging to the same age class (adults) except for I. punctatus, for which comparable concentrations in both young and old animals were found.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with other studies (Jovičić et al 2015;Léopold et al 2015;Jia et al 2017), we found only a few significant relationships between metal concentrations and total length (a proxy for age). In line with previous literature (Rakocevic et al 2018), significant relationships were mainly found for essential elements, while no clear or not-significant relationships were found for the non-essentials. The absence of clear patterns is likely due to fish belonging to the same age class (adults) except for I. punctatus, for which comparable concentrations in both young and old animals were found.…”
Section: Discussionsupporting
confidence: 91%
“…The only exceptions were Mg and Co in S. glanis, which showed negative relationships, suggesting that life-history changes may play a considerable role. Previous literature showed, however, that this relationship can be highly variable (Alhashemi et al 2012;Luczynska et al 2016;Dragun et al 2016;Rakocevic et al 2018). One possible explanation is that fish could have physiological mechanisms that reduce the impact of metals on body condition (Tenji et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration levels of essential TEs (Zn > Fe > Cu > Mn) in meager muscle found in this study are similar to those described in the literature [41]. Mean Zn concentration (4.5 ± 0.7 mg kg −1 ww) is also consistent with data measured in fish from conventional aquaculture (5.3 ± 0.4 mg kg −1 ww) [17].…”
Section: Trace Elementssupporting
confidence: 90%
“…Besides, the concentration of Ni in the tissues was low, which could support the information that the highest amount of Ni was detected in the gill instead of the tissue due to the result of metallothioneins that trapped heavy metals (Saleh & Marie, 2015). Moreover, Co was not detected in any of the fish muscles, which was in agreement with the study of (Rakocevic, Sukovic, & Maric, 2018).…”
Section: Variations Of Elements In Fish Samplessupporting
confidence: 87%